Classification of competitiveness determinants in information and communication technologies (Economics and region, 2024)
In the current era, the influence of the ICT sector on the national economy is greater than ever before. Consequently, it is vital to gain a deeper understanding of the various factors that affect ICT companies and the ICT sector in order to ensure the continued growth and competitive advantage of the national economy. It is therefore necessary to consider, summarise, group and classify the principal determinants of influence on the development and competitiveness of information and communication technologies (at the level of ICT companies and the ICT sector as a whole) for subsequent use by the main stakeholders. The objective of this study is to identify the distinctive characteristics and classify the factors that influence the development and competitiveness of information and communication technologies (ICT) at the level of individual ICT companies and at the level of the broader ICT sector within a national economy. It is proposed that the determinants of the development and competitiveness of ICT companies be classified according to the following criteria: the Five Competitive Forces Model, the Diamond Model, the Value Chain Model, the formation environment (to take into account the internal environment of the ICT company, its external industry environment or in the national/global context), types of resources (to reflect the impact of resources on the ICT company's competitive position), impact duration (to help ICT companies prioritise their corporate strategies), strategic focus (to align corporate activities with selected competitive advantages), types of technology (to understand the specific challenges and opportunities of different technologies), and types of market factors (to understand the challenges and opportunities of target markets). Concurrently, the categorisation of determinants of development and competitiveness within the ICT sector of the national economy is constituted by a set of elements pertaining to the economic environment (for the purpose of identifying the particular economic circumstances that impact upon the ICT sector), the technological environment (for the purpose of understanding the specific technological factors and innovations that contribute to its growth and competitiveness), the social environment (for the purpose of characterising the influence of social factors on the implementation and utilisation of ICT), the regulatory environment (for the purpose of considering the impact of legislation, regulations and policies on the ICT sector) and market dynamics (for the purpose of reflecting the impact of market conditions on the ICT sector).
Keywords: ICT sector; ICT companies; competitiveness; determinants of competitiveness; classification